A3 Exploring mitochondrial dysfunction and dynamics in HD. (13th September 2016) - Giorgini, Flaviano
Abstract : Alterations in mitochondrial function, morphology, and bioenergetics have been observed in Huntington's disease (HD) patients and models, and likely play an important role in disease onset and progression. Mitochondrial morphology is dynamic and is regulated by the opposing actions of fusion-promoting proteins (Mfn1/Mfn2, Opa1), and fission-inducing Drp1. These processes are closely linked to the clearance of damaged mitochondria via autophagy, known as mitophagy, which is a critical component of the mitochondrial quality control (MQC) system. The proteins Parkin and PINK1 play an important role in mitophagy and MQC: Parkin is a cytosolic E3 ubiquitin ligase recruited to dysfunctional mitochondria by PINK1, a serine/threonine kinase. It has recently been observed that PINK1-induced mitophagy is protective in models of HD, via improved mitochondrial function and integrity. In parallel work, we have found that overexpression of human Parkin in Drosophila models of HD reverses several disease-associated phenotypes. Using high resolution respirometry we found that mutant huntingtin fragment (mHTT) expression in muscle tissue alters mitochondrial function and mass, which is improved upon Parkin co-expression. In addition, pan-neuronal expression of Parkin ameliorated neurodegeneration and extended shortened lifespan in animals expressing mHTT in neurons. In total our work indicates that Parkin can improve HD-relevant phenotypes and provides further support for targeting mitophagy as a potential therapeutic strategy in HD.